1980
DOI: 10.1038/ki.1980.194
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of exercise training in hemodialysis patients

Abstract: The effects of 9 +/- 6 months of exercise training on lipid and carbohydrate metabolism were studied in six hemodialysis patients. Training lowered triglyceride levels 39 +/- 25% (P less than 0.02) and increased plasma high-density lipoprotein cholesterol levels 23 +/- 22% (before, 26 +/- 5 mg/dl; after, 31 +/- 8 mg/dl; P less than 0.05). There was a 23% improvement in glucose tolerance (P less than 0.01) and a 40% reduction in hyperinsulinism (P less than 0.01) with no significant changes in body weight or di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
109
1
7

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(129 citation statements)
references
References 20 publications
12
109
1
7
Order By: Relevance
“…These studies have generally been conducted among the general population, and the few studies conducted among renal disease patients relied on self-reported rather than directly measured activity. Increasing physical activity has a number of well described beneficial physiologic effects on cardiorespiratory fitness, endothelial function (11), BP (12), dyslipidemia (13), muscle strength, and inflammation (14), among others. These effects offer plausible biologic pathways to explain the relationship of greater physical activity with lower risk of mortality.…”
mentioning
confidence: 99%
“…These studies have generally been conducted among the general population, and the few studies conducted among renal disease patients relied on self-reported rather than directly measured activity. Increasing physical activity has a number of well described beneficial physiologic effects on cardiorespiratory fitness, endothelial function (11), BP (12), dyslipidemia (13), muscle strength, and inflammation (14), among others. These effects offer plausible biologic pathways to explain the relationship of greater physical activity with lower risk of mortality.…”
mentioning
confidence: 99%
“…Entre las características de todos ellos, destaca la gran heterogeneicidad de los mismos, fundamentalmente en cuanto al tipo y duración del ejercicio realizado así como a los distintos estudiajes del paciente renal; si bien es cierto que la gran mayoría de los estudios se centran en la realización de ejercicio físico de predominio aeróbico durante las sesiones de HD. A pesar de ésta mencionada diversidad, la práctica totalidad de los estudios ponen de manifi esto los efectos benefi ciosos del ejercicio físico sobre la fuerza muscular y la capacidad funcional y los aspectos psicológicos (1)(2)(3)(4)(5)(6) .…”
Section: Discussionunclassified
“…Desde entonces hasta hoy, todos los estudios refi eren benefi cios del ejercicio en este tipo de pacientes tanto a nivel fi siológico, como funcional o psicológico (3)(4)(5)(6) . A pesar de todo, la implantación de programas de ejercicio en unidades de HD no está generalizada.…”
Section: Introductionunclassified
“…Improvements in HD patients' physical fitness as measured by reaction time and lower extremity muscle strength (16), left ventricular systolic function (17), and psychosocial functioning (18) have been demonstrated in randomized clinical trials. Other studies of exercise interventions in patients who were on HD have provided evidence to support improvement in arterial stiffness (19), decrease in pulse pressure (20), increase in aerobic capacity (21)(22)(23)(24)(25)(26), reduced need for antihypertensive medications (23,27,28), increase in hemoglobin concentration and hematocrit levels (28), and improved lipid metabolism (28). Started HD in hospital-based facility (%) 29.6 a CABG, coronary artery bypass grafting; HD, hemodialysis; AMI, acute myocardial infarction; COPD, chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%